2022
DOI: 10.3390/jmse10070920
|View full text |Cite
|
Sign up to set email alerts
|

Formation Control of Multiple Autonomous Underwater Vehicles under Communication Delay, Packet Discreteness and Dropout

Abstract: Effective communication between multiple autonomous underwater vehicles (AUVs) is necessary for formation control. As the most reliable underwater communication method, acoustic communication still has many constraints compared with radio communication, which affects the effectiveness of formation control. Therefore, this paper proposes a formation control scheme for multiple AUVs under communication delay, packet discreteness and dropout. Firstly, the communication delay is estimated based on the kernel densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In the future, we will verify the proposed net avoidance controls by doing experiments with real underwater robots. Also, in the future, we will extend the proposed controls to multi-robot systems [ 54 , 55 , 56 ], so that a group of multiple underwater robots can move towards a goal while avoiding underwater nets.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we will verify the proposed net avoidance controls by doing experiments with real underwater robots. Also, in the future, we will extend the proposed controls to multi-robot systems [ 54 , 55 , 56 ], so that a group of multiple underwater robots can move towards a goal while avoiding underwater nets.…”
Section: Discussionmentioning
confidence: 99%
“…However, acoustic communication also has non-negligible limitations, including delay, path loss, limited bandwidth, multipath and so on [8,9]. In practice, the propagation delay is related to the speed and distance of propagation [10]. The propagation speed of radio waves in air is equivalent to the speed of light.…”
Section: Introductionmentioning
confidence: 99%
“…This attracted attention in the above-mentioned study [20], and a solution was found by combining measurement data from acoustic sensors with information from other sensors in the onboard inertial navigation system. A more typical way to deal with delayed observations is to estimate the delay time and consider it by adjusting the usual filter [35]. Interestingly, the delay in observations is explained by nature not only for underwater observations but also in some chemical processes [36].…”
Section: Introductionmentioning
confidence: 99%